Pestisitlerin Farklı Bacillus spp. Gelişimi Üzerine Etkilerinin Belirlenmesi - Kızılkaya, Rıdvan; Aksoy, H. Murat (My University, 1999)
Bu çalışmada pestisitlerin farklı konsantrasyonlarının (0, 0.5, 1.0, 1.5, 2.0 ve 2.5 ppm) Bacillus spp. gelişimi üzerine olan etkileri invitro koşullarında araştırılmıştır. Bakterisitin (Streptomycin)'in tüm uygulama konsantrasyonlarında Bacillus spp. gelişiminin engellendiği, buna karşın insektisit (Karate 5 EC), fungisit (Tachigaren 30 L) ve herbisit (2,4-D) etkilerinin değişkenlik gösterdiği saptanmıştır. B. cereus var. mycoides ve S. pumilus gelişimini insektisit ve fungisitin artırdığı, herbisitin ise azalttığı belirlenmiştir. Toksin üreterek patojen olan S. sphaericus ırk 2362 ve 1593'ün gelişimlerini insektisitin artırdığı, fungisit ve herbisitin ise azalttığı, buna karşın 6. thuringiensis var. israelensis gelişimini ise herbisit ve insektisitin artırdığı, bakterisit ve fungisitin ise azalttığı saptanmıştır.

: In this research, the effects of different concentrations of pesticides (0,0.5,1.0,1.5, 2.0 and 2.5 ppm) on the growth of Bacillus spp. invitro were investigated. As a result of this research, the effects of insecticide (Karate 5 EC), fungicide (Tachigaren 30 L) and herbicide (2,4-D) on the growth of Bacillus spp. varied depending upon application concentrations, whereas bactericide (Streptomycin) prevented to the growth of Bacillus spp. in all concentrations. It was found that insecticide and fungicide increased the growth of S. cereus var. mycoides and 6. pumilus while herbicide decreased it. The growth of B. sphaericus strain 2362 and 1593, which are being patogen by producing toxin, was increased by insecticide while decreased by fungicide and herbicide. Bactercide and fungicide had negative effect on the growth of B. thuringiensis var. israelensis, although herbicide and insecticide had a possitive effect.
Determination of the effects of pestdicides on the growth of different Bacillus spp.
Keywords: Ziraat Mühendisliği